2006
DOI: 10.4049/jimmunol.177.6.4080
|View full text |Cite
|
Sign up to set email alerts
|

Induction of RelB Participates in Endotoxin Tolerance

Abstract: Using a THP-1 human promonocyte model of endotoxin tolerance that simulates the sepsis leukocyte phenotype, we previously showed that tolerant cells remain responsive to LPS endotoxin with degradation of IκB in the cytosol and nuclear translocation and accumulation of p50 and p65 NF-κB transcription factors. Despite this, endotoxin-inducible NF-κB-dependent innate immunity genes, like IL-1β, remained transcriptionally unresponsive in the tolerant phenotype, similar to the endotoxin tolerance observed in sepsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
110
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(124 citation statements)
references
References 59 publications
10
110
3
1
Order By: Relevance
“…In this model, levels of p65 and p50 were not changed by endotoxin tolerance. Overexpression of RelB in THP-1 cells mimics the phenotype of endotoxin tolerance and vice versa, inhibition of RelB abolished the induction of tolerance (21). We observed a moderate ϳ2-fold increase in general DNA binding of p65 and p50 under conditions of endotoxin tolerance and, in agreement with the findings of Yoza et al (21), a highly significant 4-fold induction of p52 DNA binding.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In this model, levels of p65 and p50 were not changed by endotoxin tolerance. Overexpression of RelB in THP-1 cells mimics the phenotype of endotoxin tolerance and vice versa, inhibition of RelB abolished the induction of tolerance (21). We observed a moderate ϳ2-fold increase in general DNA binding of p65 and p50 under conditions of endotoxin tolerance and, in agreement with the findings of Yoza et al (21), a highly significant 4-fold induction of p52 DNA binding.…”
Section: Discussionsupporting
confidence: 81%
“…Overexpression of RelB in THP-1 cells mimics the phenotype of endotoxin tolerance and vice versa, inhibition of RelB abolished the induction of tolerance (21). We observed a moderate ϳ2-fold increase in general DNA binding of p65 and p50 under conditions of endotoxin tolerance and, in agreement with the findings of Yoza et al (21), a highly significant 4-fold induction of p52 DNA binding. In endotoxin-tolerant THP-1 cells, RelB was found to associate with p65, resulting in a repression of the IL-1␤ promoter activity (21,34).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our previous studies showed that RelB knockdown induced p65 binding to the proximal promoters of TNF␣ and IL-1␤ and, consequently, reactivated their transcription (27,42). To assess whether nucleosome repositioning to the permissive locations seen in T0 and T1 cells after RelB knockdown was associated with the induction of p65 binding, we measured p65 binding to the proximal NF-B (K3) site, which we previously showed is required for the transcription activation (27).…”
Section: Baf Chromatin-remodeling Complex Is Required For Nucleosome mentioning
confidence: 99%